Moore-Penrose invertibility in involutory rings: the case aa+=bb+ - Patrício, Pedro (2010)
In this article, we consider Moore-Penrose invertibility in rings with a general involution. Given two von Neumann regular elements a, b in a general ring with an arbitrary involution, we aim to give necessary and sufficient conditions to aa† = bb†. As a special case, EP elements are considered.